The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1590/s0037-86822009000100018
|View full text |Cite
|
Sign up to set email alerts
|

Impacto do laser de baixa intensidade na supressão de infecções pelos vírus Herpes simplex 1 e 2: estudo in vitro

Abstract: The use of low-level laser to suppress infections caused by Herpes simplex viruses 1 and 2 was evaluated after one to five applications. A gradual reduction in replication of Herpes simplex viruses 1 and 2 was observed, with 68.4% and 57.3% inhibition, respectively, after five applications, thus favoring its clinical use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 9 publications
0
7
0
2
Order By: Relevance
“…However, its efficacy in long-term suppression of herpes simplex infections has yet to be established. In vitro and in vivo studies have been conducted 7,8 and positive outcomes have been shown to be directly related to the number of treatment sessions and the virus type.…”
Section: Casementioning
confidence: 99%
See 3 more Smart Citations
“…However, its efficacy in long-term suppression of herpes simplex infections has yet to be established. In vitro and in vivo studies have been conducted 7,8 and positive outcomes have been shown to be directly related to the number of treatment sessions and the virus type.…”
Section: Casementioning
confidence: 99%
“…LLLT treatment sessions were performed in accordance with the in vitro study previously reported by Ferreira et al and with the regimen described by the manufacturer. The two cases studied indicate the need for longitudinal studies, in order to establish LLLT treatment protocols for infectious agents and other related microorganisms and for a range of immunosuppressed patients, for whom a generally accepted treatment course has yet to be descriebd 7 .…”
Section: Casementioning
confidence: 99%
See 2 more Smart Citations
“…O LBI tem sido bastante empregado na prática clínica de diversas áreas da saúde, devido aos seus efeitos anti-inflamatório, analgésico, antiedematoso e de contribuição para o reparo tecidual. Entre os efeitos citados pode-se incluir também a degranulação de mastócitos, o aumento da circulação periférica, a vasodilatação e a proliferação fibroblástica [5]. Muitas pesquisas, in vitro e in vivo, vêm sendo realizadas sobre LBI e seu uso terapêutico.…”
Section: Introductionunclassified